The Effect of Olive Fruit Fly Bactrocera oleae (Rossi) Infestation on Certain Chemical Parameters of Produced Olive Oils - Valenčič, Vasilij (Molecules, 2020)
Olives affected by active and damaging infestation (olive fruit fly Bactrocera oleae (Rossi)) were assayed for their chemical composition. Biophenols were determined by HPLC, sterols, triterpenic dialcohols, and fatty acids by gas chromatography analysis. The acquired data were statistically analyzed. Oils produced from “Istrska belica” fruit affected by active infestation compared to the oils made from fruit affected by damaging infestation showed higher amounts of total oleuropein biofenols (377.3 versus (vs.) 106.6 mg/kg), total biophenols (755 vs. 377 mg/kg), lignans (85.3 vs. 32.9 mg/kg), the dialdehydic form of decarboxymethyl oleuropein aglycone (DMO-Agl-dA) (148.3 vs. 49.0 mg/kg), its oxidized form (DMO-Agl-dA)ox (35.2 vs. 8.5 mg/kg), the dialdehydic form of oleuropein aglycone (O-Agl-dA) (61.1 vs. 8.0 mg/kg), the dialdehydic form of ligstroside aglycone (L-Agl-dA) (63.5 vs. 28.0 mg/kg), the aldehydic form of oleuropein aglycone (O-Agl-A) (40.6 vs. 8.4 mg/kg), and lower amounts of tyrosol (Tyr) (6.0 vs. 13. 9 mg/kg) and the aldehydic form of ligstroside aglycone (L-Agl-A) (13.8 vs. 40.3 mg/kg). Higher values of stigmasterol (2.99%) and lower values of campesterol (2.25%) were determined in oils affected by damaging infestation; an increase in triterpenic dialcohols was also observed (3.04% for damaging and 1.62% for active infestation). Oils affected by damaging infestation, compared to active infestation, showed lower amounts of oleic acid (73.89 vs. 75.15%) and higher amounts of myristic (0.013 vs. 0.011%), linoleic (7.27 vs. 6.48%), and linolenic (0.74 vs. 0.61%) acids.